Do the Physcians Defend Euthanasia - Gündüz, Tarık; Öner, Setenay; Çınar, Tuncay (The Bulletin of Legal Medicine, 1996)
In this study, after the definition and short historical development of Euthanasia, a questionnaire was given to 510 medical staff; 208 of whom are medical students who are in the 5th form and 302 of whom are physcians. In this questionnaire 6 multiple choice questions were asked about the knowledge level, social groups to comment and argue on the subject, the right of person to decide about his/her own life, opinions about current applications of euthanasia, whether he/she would agree on the application of the process and whether he would accept to get a responsibility in it or not. It was determined that among the people who attended the questionnaire, one third didn’t have enough knowledge about the subject while 325 (63.72 %) of them supported the application, still 351 (68.82 %) of them refused to get a responsibility in the application of euthanasia, even if the process becomes legal. Opinions of the people who are with and against the idea were collected and summarized, it was determined that although passive euthanasia is not legal it is currently being applied when it is necessary and that physcians are biased to the legalization of the subject while they refuse to take a role in the application. Keywords : Euthanasia, Self Deliverance, Right to Life, Mercy Killing, Informed Consent